2010
DOI: 10.1515/secm.2010.17.3.191
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Microwave Sintering on the Properties of Electroless Ni Plated WC-Fe-Ni Composites

Abstract: Ni-Fe metal matrix composites reinforced with WC have been fabricated by microwave sintering at various temperatures. A uniform nickel layer on WC and Fe powders was deposited prior to sintering using electroless plating technique, allowing closer surface contact than conventional methods such as mechanical alloying. The reactivity between WC and Fe powders to form carbides of Fe is controlled through Ni layer existing on the starting powders. A composite consisting of quaternary additions, WC, Ni and Fe was p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 1 publication
0
5
0
Order By: Relevance
“…The density values are also very similar to studies regarding WC-Co composited by Agrawal et. al., 1999 andYönetken andErol, 2010..The thickness of Ni layer can have an influence on the density; as it increases the number of pores can drop to a limited extend since but the density measured would be lower than the theoretical density of (WC)Ni that is nearly 14.28 g/cm 3 . The shape distribution of powders in 10 μm (WC)Ni composite appears to be irregular unlike of 2 μm (WC)Ni composite, which may have a slight effect on the number of pores and hence their density at both temperatures.…”
Section: Density Of (Wc)ni Compositesmentioning
confidence: 89%
See 2 more Smart Citations
“…The density values are also very similar to studies regarding WC-Co composited by Agrawal et. al., 1999 andYönetken andErol, 2010..The thickness of Ni layer can have an influence on the density; as it increases the number of pores can drop to a limited extend since but the density measured would be lower than the theoretical density of (WC)Ni that is nearly 14.28 g/cm 3 . The shape distribution of powders in 10 μm (WC)Ni composite appears to be irregular unlike of 2 μm (WC)Ni composite, which may have a slight effect on the number of pores and hence their density at both temperatures.…”
Section: Density Of (Wc)ni Compositesmentioning
confidence: 89%
“…In this technique, the coating occurs as a result of the chemical reaction from which Ni is released and a homogeneous deposition of Ni layer onto WC particles takes place without an electric current. During the manufacture of composites, Ni coating functions as a binder between ceramic powders as well as acts as a filler metal for the pores between powders (Yönetken and Erol, 2010). The size WC powders were chosen to be 2 and 10 µm to investigate the effect of powder size of matrix on the bonding capacity and reduction of the pores within the matrix.…”
Section: Experimental Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The increase in microhardness by heat treatment can be related to transforming the amorphous structure into a crystalline one [18]. Yönetken [25] indicated that Ni plating of powders results in higher hardness values. The protruding tip of the hardness tester generates a limited deformation because of the readily deformable Ni layer existing on the particles and therefore results in higher hardness readings in Ni plated specimens, whereas the protruding tip of the hardness tester causes a complete deformation and breaks apart the particles in non-plated specimens, lowering the hardness readings Fig.…”
Section: Microhardnessmentioning
confidence: 99%
“…Small-grain metallic materials with high strength are both theoretically and experimentally interesting. It is possible to improve the mechanical properties due to the strengthening of the ceramic particles [12][13][14][15][16][17]. Commonly used carbide ceramics due to abrasion resistance have often been used in cutting tools [18][19][20].…”
Section: Introductionmentioning
confidence: 99%